Influence of Leadership and Environmental Excellence SME Towards Operational Excellence In Bandung District - Andri Irawan; Eka Ludiya (Proceeding International Conference on Information Technology and Business, 2018)
Global competition very tight making SMEs should make a different value that reflects an advantage to win the competition of competitors. The research objective to be achieved is to measure and determine how much influence the leadership and environmental excellence towards operational excellence. Type of research is the study of cause and effect. The sampling method used by the researchers is nonprobability sampling with accidental sampling method. Test instrument instrument using validity and reliability. The analytical tool used in the study are SEM Pls. The results showed that the leadership had a significant influence on the operational excellence that is equal to 0,265, or 26.5%, this suggests that SMEs concluded that aspects of leadership including the important things that must be considered. Environmental excellence provide no significant effect on the operational excellence that is equal to 0.230 or 23%, this shows that SMEs have not been able to optimize its operations. Simultaneously leadership and environmental excellence gives the effect of 0,142 or 14.2%, this suggests that operational excellence is heavily influenced by other factors not examined.Keywords: Leadership, Environmental Excellence, Operational Excellence, and SME